Trocas de carbono atmosférico sobre dois diferentes sistemas de plantio de milho no sul do Brasil - Teichrieb, Claudio Alberto (2012)
Farming systems can act as a source or sink of atmospheric carbon, depending on the type of culture and soil management system adopted. This thesis presents a comparative study between the data obtained from two micrometeorological stations installed on the corn crop, in order to assess the impact of two tillage systems for corn (conventional tillage-CT and no-till-NT) in net ecosystem exchange of carbon fluxes (NEE). The flux were evaluated by the method of eddy covariance (EC), during the 156 days of maize. The results show that the two systems of planting corn act as drain CO2 −C and that there is a difference in the absorption ofCO2−C between the two planting systems with a NT with higher net exchange of carbon in the ecosystem in relation to CT . The biggest difference between the systems occurs in the first half cycle of corn, and after 40 days the cultures behave as a source of CO2−C, with higher values of CT issue at this time in relation to NT, and from then culture behaves as CO2−C drain. We conducted a study on the relative role of low-frequency and turbulent processes in the nocturnal boundary layer through the analysis of two-point correlations of wind components. Noting that the low-frequency processes dominate the two-point correlations in weak wind conditions, that the vertical two-point correlations of the spanwise component are negative at the very low time scale limit and that the statistical properties of the turbulent field are preserved horizontally over distances for which the two-points correlation have already been largely reduced.